1999
DOI: 10.1139/z99-173
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic plasticity in the labral fan of simuliid larvae (Diptera): effect of seston load on primary-ray number

Abstract: The number of primary rays in the labral fan of filter-feeding black fly (Diptera: Simuliidae) larvae has been used by some authors to aid in species identification. We examined the number of primary labral fan rays in field-collected last-instar larvae of Simulium rostratum and Simulium decorum. Significant inter- and intra-specific differences were found both spatially and temporally. Simulium rostratum and S. decorum larvae were also reared to last instar (from eggs or first- or second-instar larvae) under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Thus, by adjusting the trait flexibility of fan structure, the larvae reduced production and maintenance costs and optimized feeding function according to food availability and current velocity. Lucas and Hunter (1999) demonstrated that the ray number of Simulium rostratum and Simulium decorum decreased with food supply increase in a laboratory experiment. In a study on another blackfly species, Simulium lundstromi, phenotypic plasticity of the fan structure showed a similar pattern as found in S. noelleri in response to different current velocities (Zhang and Malmqvist 1997).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, by adjusting the trait flexibility of fan structure, the larvae reduced production and maintenance costs and optimized feeding function according to food availability and current velocity. Lucas and Hunter (1999) demonstrated that the ray number of Simulium rostratum and Simulium decorum decreased with food supply increase in a laboratory experiment. In a study on another blackfly species, Simulium lundstromi, phenotypic plasticity of the fan structure showed a similar pattern as found in S. noelleri in response to different current velocities (Zhang and Malmqvist 1997).…”
Section: Discussionmentioning
confidence: 94%
“…The resourcebased divergent selection on some phenotypic traits in different environments is important for speciation to occur (Schluter 1996;Losos et al 1997;McKinnon et al 2004). The function of the fan morphological traits of different species is directly correlated with the flux rate of food particles (Zhang 2000;Lucas and Hunter 1999). Large fans in slow currents are beneficial to permit high particle delivery rate (Lacoursie`re and Craig 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, larvae often demonstrate strong preferences for a restricted range of ambient velocities (Lacoursière 1992;Fonseca and Hart 1996) and exhibit spatial patterns within aggregations (Hart 1986;Ciborowski and Craig 1989) that may allow them to achieve higher ingestion rates. Moreover, experimental studies have demonstrated that the morphology of feeding structures (=labral fans) can be a phenotypically plastic response to variations in ambient flow conditions Malmqvist 1996, 1997;Palmer and Craig 2000) or seston loads (Lucas and Hunter 1999;Palmer and Craig 2000). Collectively, these results support the view that natural selection has molded the behavior and morphology of black flies to increase larval ingestion rates, and imply that flow will be a critical factor affecting feeding and associated processes (e.g., benthic-pelagic coupling, habitat selection, and growth).…”
Section: Introductionmentioning
confidence: 99%
“…Labral fan morphology was assessed by measuring the fan ray width and length and number of rays of the completely opened primary fan, under a compound microscope using a microscopic micrometer. As intraspecific variation of the labral fan morphology has been reported (Lucas & Hunter, 1999;Adler et al, 2004), we selected larvae from several sampling sites for morphological measurement. For each species, at least 30 larvae were measured.…”
Section: Black Fly Trait Datamentioning
confidence: 99%